(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The object of the research are the social entrepreneurs and its business development. The aim of the research is to discuss existing marketing strategies applied to social entrepreneurship and to offer possible ways of their improvement. The research is relevant and consistent with the increasing role of social entrepreneurship taking the full power throe the fast changing political, economic, socio cultural and technological circumstances of the 21st century. While marketing the social entrepreneurship, the focus on marketing strategies must be revised. The research methodology includes both traditional and modern elements of marketing, such as marketing mix, strategies, customer segmentation and targeting, pricing altogether with the main elements of social entrepreneurship, such as social and economic aspects. The results present thet in standard marketing strategies, the strategy for social entrepreneurs should include segmentation of the customers and consumers by taking into consideration standard criteria (such as geographical, demographical, psychographic and behavior segmentation) but also implementing own criteria most adequate for the products they are currently interested to produce. It is important which factors are significant enough to take decisions of expansion, harvest or liquidation of products.